Analysis of synergies and trade-offs between animal welfare, ammonia emission, particulate matter emission and antibiotic use in Dutch broiler production systems. (April 2021) - Vissers, Luuk S.M.; Saatkamp, Helmut W.; Oude Lansink, Alfons G.J.M.
Abstract: Context: Intensive broiler production systems are criticized by EU citizens because of their negative impact on animal welfare, the environment and human health. Objective: To inform the development of sustainable broiler production systems, this paper provides insight in the synergies and trade-offs between different external factors originating from broiler production systems by developing a new analysis approach. Methods: The approach was applied to the Dutch conventional, New Dutch Retail Standard and Extensive Indoor+ systems. The latter two systems have more stringent standards on animal welfare relative to the conventional system. Four external factors were considered, i.e. animal welfare (indicated by Welfare Quality Index score), ammonia emission (kg NH3 /animal place/year), particulate matter emission (g PM10 /animal place/year) and antibiotic use (defined daily doses animal). Results and conclusions: Results show that the shift from a fast-growing breed towards a slower-growing breed caused synergy by improving animal welfare and lowering antibiotic use. Furthermore, the reduction in protein content of the feed, and possibly the reduction in stocking density, caused synergy by enhancing animal welfare and lowering ammonia emission. System changes that stimulated activity, such as the reduction in stocking density, enhanced animal welfare but caused a trade-off with particulate matter emission. Although the New Dutch Retail Standard and Extensive Indoor+ system were characterized by a higher ammonia and particulate matter emission per animal place per year relative to the conventional system, experts estimated that these emissions were partially (New Dutch Retail Standard) or fully (Extensive Indoor+) offset at farm level via a lower stocking density. Overall, we conclude that future development of broiler production systems can exploit the synergy between animal welfare, antibiotic use, and ammonia emission and minimize the trade-off between animal welfare and particulate matter emission. Significance: The insights obtained from this paper can support the development of sustainable broiler production systems that minimize external factors originating from these systems. Graphical abstract: Unlabelled Image Highlights: Broiler production systems are criticized because of their negative impact on animal welfare and the environment. Synergies and trade-offs between external factors originating from Dutch broiler production systems were analyzed. Synergies were found between animal welfare and antibiotic use, trade-offs between animal welfare and PM10 emission. We conclude that future broiler production systems can exploit synergistic effects and minimize the trade-offs. Insights can support the development of sustainable broiler production systems.